Estudo retrospectivo, índice AgNOR e níveis séricos de vitamina D em cães com mastocitoma - Mann, Thaís Rapachi (2016)
Mast cell tumors (MCT) are neoplastic tumors of mast cells of unknown etiopathogenesis, representing up to 21% of all canine cutaneous cancers. This tumor varies widely in biological presentations and behaviors, ranging from benign to extremely aggressive, leading to metastasis and death. The cytological identification of MCT is a highly recommended method for initial detection of the tumor, it is inexpensive, can be performed with conscious animal and allows to suspect a tumor of high degree according to the cellular features. In addition to the histological grading, which is the gold standard for establishing the prognosis of MCT, additional markers are recommended, among them the AgNOR count, an indicator of cell proliferation. Additionally, some studies focus on the relationship between MCT and vitamin D, since mast cell tumors express vitamin D receptors (VDR). Thus, the aim of this research is to characterize the occurrence of canine MCT diagnosed by cytological examination in the region of Santa Maria/RS, to describe a protocol for determining AgNOR index in cytological samples of MCT and to investigate the relationship between vitamin D levels and AgNOR index in dogs with this tumor, since the AgNOR index is already consolidated as a prognostic marker for mastocytoma and vitamin D has been reported as a target for MCT management. Regarding to the occurrence profile of this tumor, we found results similar to those described in the literature, with some peculiarities referring to breeds and clinicopathological findings, allowing to suspected of MCT and planning more appropriate therapeutic interventions for each case. Referring to the AgNOR index, a protocol adapted from techniques already described was applied to cytological samples. Also has been observed that vitamin D and AgNOR index in dogs with MCT are negatively and moderatelycorrelated (P=0,011), suggesting that vitamin D levels can be measured in dogs with this tumor. In addition, follow-up studies of dogs with MCT and monitoring their outcoming are necessary, so that the vitamin D can be proposed as a prognostic marker and therapeutic agent for this neoplasm.